AGE-VARYING ASSOCIATIONS BETWEEN PERCEIVED CONTROL, HEALTH, AND COGNITION IN OLDER ADULTHOOD. (16th November 2018) - Lee, J; Chopik, W
Abstract: Perceived control (i.e., mastery) has been recognized as a key psychological component of successful aging and is consequential for many health outcomes in later life. However, it is still unknown whether and how the associations between perceived control and health outcomes will differ throughout mid-to-late adulthood for individuals in different ages. Utilizing cross-sectional data of Americans aged over 50 from Health and Retirement Study (HRS), we used the time-varying effect model (TVEM) to examine how the strength of an association changes by age. We examined whether the link between perceived control (i.e., mastery and constraints) and health outcomes (i.e. self-rated health, cognitive functioning, depressive symptoms, and chronic conditions) showed age-related differences from ages 50 to 95 and whether socio-demographic characteristics moderated these age-related differences. Mastery/constraints and health, cognition, depression, and chronic conditions were associated in intuitive ways that were consistent with previous research. However, the magnitude of the association between mastery and depression and chronic conditions decline in more advanced ages. Likewise, the magnitude of the association between constraints and health, depression, and chronic conditions also diminished in size of time. The remaining associations were invariant across the second half of life. There were consistent difference between races, where the most association were weaker for non-Whites compared to Whites. For example, the association between mastery/constraints and health/cognition was smaller for non-White compared to Whites, suggesting an environmental suppression effect. TVEM provides, with great specificity, an opportunity to uncover the exact ages under which these associations change across the lifespan.